2017
DOI: 10.1051/epjconf/201714006001
|View full text |Cite
|
Sign up to set email alerts
|

Does modifying the particle size distribution of a granular material (i.e., material scalping) alters its shear strength?

Abstract: Abstract. By means of two dimensional contact dynamics simulations, we analyzed the effect of the particle size distribution (PSD) on the shear strength of granular materials composed of un-breakable disks. We modelled PSDs with a normalized beta function, which allows for building S-shaped gradation curves, such as those that typically occur in soils. We systematically controlled and varied the size span and the shape of the PSD, and found that the shear strength is independent both characteristics. This impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…It is established that the strength properties of granular media result from the build-up of anisotropic structures of geometrical and mechanical origins (Rothenburg & Bathurst, 1989). The independence of strength with PSD in the case of mono-shaped particles has been discussed previously in the literature in Azema et al (2017), Azéma et al (2017), Estrada (2016), Voivret et al (2009), Nguyen et al (2015), and Cantor et al (2018). It has been attributed to a compensation mechanism which involves both the contact orientation anisotropy which decreases with the size span, and the branch length anisotropy which behaves inversely.…”
Section: Mechanical Behaviourmentioning
confidence: 87%
See 1 more Smart Citation
“…It is established that the strength properties of granular media result from the build-up of anisotropic structures of geometrical and mechanical origins (Rothenburg & Bathurst, 1989). The independence of strength with PSD in the case of mono-shaped particles has been discussed previously in the literature in Azema et al (2017), Azéma et al (2017), Estrada (2016), Voivret et al (2009), Nguyen et al (2015), and Cantor et al (2018). It has been attributed to a compensation mechanism which involves both the contact orientation anisotropy which decreases with the size span, and the branch length anisotropy which behaves inversely.…”
Section: Mechanical Behaviourmentioning
confidence: 87%
“…Numerical research 2D and 3D suggest that steady-state shear strength is independent of PSD for materials composed of unbreakable particles with similar shape across sizes (monoshaped) (Azema et al, 2017;Azéma et al, 2017;Estrada, 2016;Voivret et al, 2009;Nguyen et al, 2015;Cantor et al, 2018). This non-intuitive result motivated the investigation of particle size-shape correlation effects in greater detail in this research.…”
Section: Introductionmentioning
confidence: 84%
“…Numerical analysis to investigate the effect of only PSD alteration on shear strength, isolating the phenomenon from the influence of particle shape using the discrete element method (DEM), reveals that the steady state shear strength is invariant when altering the PSD in the specific case where the shape of the particles is kept constant across sizes and in the absence of crushing (Azéma et al 2017a(Azéma et al , 2017bEstrada 2016;Voivret et al 2009;Nguyen et al 2015;Cantor et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a summary of the main findings of a research project conducted to investigate when, why and how scaling of coarse granular materials affects its shear strength. Key outcomes of the project are separately published in Linero et al (2017Linero et al ( , 2019c and Azéma (2017aAzéma ( , 2017b, or under review for publication in Linero et al (2019aLinero et al ( , 2019b. This summary is drawn from each of these to provide specific advice to mine dump designers and operators, in a forum of geotechnical engineers who can appreciate the application of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the effect of the PSD on the critical state is yet inconclusive based on the existing studies in literature. Some studies indicated that the critical state friction angle was related to PSD [17,18], while others [19,20] found that varying PSD had little influence on the critical state friction angle. Although it is widely accepted that PSD does have influence on the CSL location in e-p' plane [21][22][23][24][25][26], how the position of CSL in e-p' plane is influenced remains unclear.…”
Section: Introductionmentioning
confidence: 99%